Is a New High-Resolution Probe Better than the Standard Probe for 3D Anal Sphincter and Levator Ani Imaging?. (April 2015) - Rostaminia, Ghazaleh; White, Dena; Quiroz, Lieschen; Shobeiri, S. Abbas
The aim of our study was to determine the accuracy of a new three-dimensional (3D) endoluminal ultrasound probe in assessing the levator ani muscle and anal sphincter complex. A total of 85 patients who had undergone concurrent 3D endovaginal (EVUS) and 3D endoanal (EAUS) ultrasound with both the standard BK 2052 probe and the new high-definition BK 8838 probes were included. For EVUS volumes, the levator ani deficiency (LAD) scores were calculated for each probe. For the EAUS volumes, any defects in the external anal sphincter (EAS) and the internal anal sphincter (IAS) visualized with each probe were recorded. The 3D volumes were evaluated in a blinded fashion. Appropriate statistics were utilized to assess absolute agreements between each pair of imaging modalities. The mean age of the patient population was 59 years ( SD ± 10.76), the mean body mass index (BMI) was 28.36 ( SD ± 5.99), and the median parity was 2 (range 1, 7). In all, 93% of the patients were Caucasian, 31% had stage 0 or 1 prolapse, while 59% had stage 2 prolapse. The mean total LAD score obtained on EVUS with the standard and the new probes were 11.49 ( SD ± 4.94) and 11.53 ( SD ± 5.01), respectively, p = 0.3778. Among the 53 patients who had EAUS with both probes, exact agreement for visualization of EAS and IAS for the standard and the new probes was 83% and 98%, respectively. Both transducers can be used for endovaginal imaging of the levator ani muscles interchangeably. Both transducers can be used for endoanal imaging of anal sphincter complex interchangeably.